Significance of Altered Carbon Flow in Aromatic Amino Acid Synthesis: an Approach to the Isolation of Regulatory Mutants in Pseudomonas aeruginosa - Calhoun, Davis H. (1972)
Pseudomonas aeruginosa displays a native resistance to a variety of inhibitory compounds, including many analogues of amino acids, purines, and pyrimidines. Therefore, it has been difficult to isolate analogue-resistant regulatory mutants which have been so valuable in other microbial species for the study of enzyme control mechanisms and for the study of amino acid transport and its regulation. However, we have found that increased sensitivity to growth inhibition by analogues can be demonstrated by manipulation of the nutritional environment. When P. aeruginosa is grown with fructose as the nutritional source of carbon and energy, the cells become sensitive to growth inhibition by β-2-thienylalanine and p-amino-phenylalanine, analogues of phenylalanine and tyrosine, respectively. Thus, mutants were isolated which are resistant to growth inhibition by β-2-thienylalanine and p-amino-phenylalanine when fructose is the carbon source, and many of the β-2-thienylalanine-resistant mutants overproduce phenylalanine. Several lines of evidence suggest that the increased sensitivity to growth inhibition by analogues of phenylalanine and tyrosine reflects a decreased rate of synthesis of aromatic amino acids or their precursors when fructose is the carbon source. This general approach promises to be valuable in the study of regulatory phenomena in microorganisms which, like P. aeruginosa, are naturally resistant to many metabolite analogues.